Feed resources availability, utilization and marketing in central and eastern Tigray, northern Ethiopia - Tesfay, Y.; Gebrelibanos, A.; Woldemariam, D.; Tilahun, H. (International Livestock Research Institute, 2016)
This survey explored the situation of different feed resources for ruminant livestock in two zones (central and eastern) in Tigray region of northern Ethiopia. These two zones account for the region’s 12% of the total land mass, 23% of the human population, 28% of the cattle population, and 56% of the small ruminant population.